Association between meeting 24-hour movement behavior guidelines and quality of life in adolescents with idiopathic scoliosis - Xinchang Sun; Lei Yang; Zhixiang Zhu; Wanxin Wang; Liwan Zhu; Shuwen Dong; Lan Guo; Liwen Yang; Yi-Fan Lin; Xiaosheng Chen; Weijun Wang; Xinhai Lu; et al. (BMC, 2024)
Abstract Background Meeting the 24-hour movement behavior (24-HMB) guideline helps enhance quality of life (QOL) of adolescents. This study aimed to assess the associations between the 24-HMB (physical activity, screen time, sleep) and QOL among adolescents with idiopathic scoliosis. Methods A cross-sectional study was conducted between September 2021 and September 2023. 24-HMB, QOL and demographic variables were collected through a self-reported questionnaire. Linear regression models and stratified analyses were used to explore statistical associations between the 24-HMB and QOL. Results A total of 1073 participants aged 10-18 years with a spinal Cobb angle between 10° and 40° were included. Overall, 20 participants (1.9%) met all three behavioral guidelines, and 272 participants (25.3%) met none. Compared to those who did not meet any of the guidelines, adolescents meeting both screen time and sleep duration (β = 4.10, 95% CI: 2.02-6.18, P < 0.001) and all 3 guidelines (β = 4.39, 95% CI: 0.27-8.51, P = 0.037) had higher QOL scores. Stratified analyses showed that the above associations were more pronounced in adolescents without back pain or with good self-image. Conclusions These findings highlight the importance of adopting and maintaining healthy behavioral habits in order to improve QOL among adolescents with idiopathic scoliosis, especially in those without back pain or with good self-image.